THE IMPACT OF COVID 19 TOWARD ECONOMIC’S COUNTRY OF SINGAPURA - Triyawan, Andi; Susilo, Adib; Afif, Mufti; Azzahra, Miftah; Prastyaningsih, Ika (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACTThis study aims to examine the effect of Covid-19 on the economy in Singapore. The method used in this study is a qualitative method using secondary data in the form of scientific journals and other literature studies. Based on the research results, the authors can conclude that the impact of the corona virus pandemic is not only on the health sector, but also all sectors are feeling the impact. Several countries that joined ASEAN had to experience a recession during the corona virus pandemic. This happens because there is a government policy in every country which requires people not to create crowds and reduce activities outside the home which causes crowds and reduces activities outside the home which causes economic processes to be hampered. This policy was made so that the spread of the corona virus can be overcome and the pandemic ends quickly so that everyone can carry out moral activities as before.Keywords: Singapore, Economic, Covid 19.